La guayaba, fuente de fenoles con actividad antioxidante - Olaya, Julio; Restrepo, Patricia; Parada, Fabián; Silva, Kelly; Espinal, Mauricio (Universidad Nacional de Colombia, 2018)
Guayaba-Psidium guajava